Pola Ritual dan Makna Simbolis Tradisi Kadiran - Norhasan, Norhasan (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
This article aims at explaining the Kadiran tradition in the village of East Kaduara, Madura. The tradition contains religious rituals in the form of selamatan or rokatan. Substantively, religious rituals of Kadiran is dhikr lead by a leader of the tarekat by reciting deeds practiced by Shaykh ?Abd al-Qâdir al-Jîlânî. The meaning of slametan Kadiran for society functions as a form of gratitude for the blessings of God. It also means that the society pray for God for His mercy and at the same time it functions as a means of balancing the needs of both physical and spiritual life. In addition, it is also aimed as a chance to meet relatives (silat al-rahim) after their daily activities and business. The Kadiran tradition, along with it specificity and uniqueness, has been well maintained by the community and in a way passed it from generation to generation, so that the tradition has existed up until the present day.